Medication adherence among hypertensive patients at Monkole Hospital Center - Baningime Monshe , Christian; Mankulu Kakumba, Jocelyn; Nsuadi Manga, Francine (Orapuh Journal, 2025)
Introduction Improving medication adherence is essential for the effective management of hypertension. Purpose This study aimed to assess the level of antihypertensive medication adherence among adult hypertensive patients at Monkole Hospital Center, evaluate their knowledge of hypertension complications, and identify predictive factors for good adherence. Methods A cross-sectional study was conducted on a sample of 121 hypertensive patients attending the Internal Medicine Department of Monkole Hospital Center from 1 August 2021 to 31 December 2021. Data were collected through interviews using a structured questionnaire. Medication adherence was assessed using the Girerd scale. Factors associated with adherence were identified using binary logistic regression analysis. Adjusted odds ratios (AOR) and 95% confidence intervals (CI) were calculated with SPSS version 25. A P-value < 0.05 was considered statistically significant. Results Among the 121 hypertensive patients, 32.2% demonstrated good adherence, 44.6% had minimal adherence problems, and 23.1% had poor adherence. Overall, 76.8% were classified as good adherents. More than half of the participants (52.9%) were female, with a mean age of 55.8 ± 10.9 years. Patients younger than 50 years (AOR = 0.136, 95% CI = 0.048–0.897, P = 0.000) and single patients (AOR = 0.086, 95% CI = 0.012–0.629, P = 0.016) were less adherent compared to those aged 50 years or older and married patients. Conclusion Patients at Monkole Hospital Center were generally classified as good adherents based on the Girerd scale. More than half of the patients were informed about their disease by doctors. Older age and being married were associated with better medication adherence.